Stretching and injury prevention in football: Current perspectives - Stojanovic, M. D.; Ostojic, S. M. (Research in Sports Medicine, 2011)
Stretching exercises are regularly recommended as a part of football-training sessions and in preparation for competition. There is little sound empirical evidence, however, to substantiate the role of stretching exercises and consequently increased flexibility on injury prevention in football. Furthermore, in the last decade or so, fundamental research has shed some light on the biomechanical adaptation of the muscle-tendon unit following different stretching protocols, improving knowledge about the topic and enabling better understanding of the stretching-injury relationship. The purpose of this review is to examine the literature on the role of stretching and/or increased flexibility on injury prevention in football, with presented results analyzed in the context of the up-to-date basic science research evidence.